The possibility of the uncanny in Andrés Ibáñez's "A master of sensations" - Trouillhet Manso, Juan (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article aims to analyze the presence of the uncanny, following Freud's approach, in  the short stories collection A master of the sensation by Andres Ibáñez. In a series of contemporary short stories residing between tradition and modernity and in an author who, due to his vitality, positivism and spiritual concerns, is difficult to associate with the uncanny. However ,the world of these stories is so varied and multiform, including disturbing stories of shadows, monsters and endless sinister motifs. Its originality lies, above all, in its novel perspective and in the combination of different elements such as eroticism, fantasy, humour, the world of comics, the macabre, vampires, meteorites and so on. In my analysis I have searched for both the aesthetic presence of his images, of a sinister nature, as well as the presence of the uncanny, in stories in which, were not to its theme or style, the disturbing appearance of the sinister would not be expected.
Keywords: Uncanny; Freud; fantastic; comedy; macabre; beauty; identity; Andrés Ibáñez